Aerobic Walking Exercise and Lifestyle Habits Interact with Sleep Quality, Stress, and Life Satisfaction: Results from a Randomized Crossover Study. Issue 3 (4th May 2021) - Wang, Feifei; Boros, Szilvia
ABSTRACT: Background : Physical exercise interacts with sleep quality, stress and life satisfaction. Purpose: The current study examined the effectiveness of regular aerobic walking on sleep quality, stress and life satisfaction and to explore the associations between lifestyle habits and sleep quality, stress and life satisfaction. Methods: A 12-week randomized cross-over study with fifty-four participants was conducted. Results: Sleep quality ( p = .002, r = −.46), stress ( p = .007, r = −.38), and life satisfaction ( p = .003, r = −.42) showed favorable changes in the intervention group and only life satisfaction increased in the control group ( p = .003, r = −.43). Alcohol consumption showed positive correlation with sleep quality ( p < .05). Males and females did not differ regarding sleep quality, stress and life satisfaction ( p > .05). Discussion: The improvement of sleep quality, stress and life satisfaction was significant in the intervention group, although changes in control group did not indicate big differences. Translation to Health Education Practice: This study provides information and guidelines for Certified Health Education Specialist to design, implement and evaluate sleep education programs. A AJHE Self-Study quiz is online for this article via the SHAPE America Online Institute (SAOI) http://portal.shapeamerica.org/trn-Webinars